2013
DOI: 10.3109/14647273.2013.800650
|View full text |Cite
|
Sign up to set email alerts
|

The case for aromatase inhibitors use in Oncofertility patients. Should aromatase inhibitors be combined with gonadotropin treatment in Breast Cancer patients undergoing ovarian stimulation for fertility preservation prior to chemotherapy? A debate

Abstract: Breast cancer is one of the hormone-dependent cancers that may be adversely affected by elevated oestrogen or progesterone concentrations, particularly the endocrine active (hormone receptor positive) breast cancers. Treatment for breast cancer patients aimed at fertility preservation, includes ovarian hyperstimulation, the harvest of oocytes, and subsequent cryopreservation of oocytes or embryos. Classically, gonadotrophins have been used effectively for ovulation induction, a treatment often accompanied by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Lower estradiol level achieved by letrozole co-treatment may potentially confer lower risk to the patient; whether it translates to better prognosis of the patients' cancer disease would require further investigation. Current studies have echoed that letrozole is both safe in terms of obstetric outcomes and decreasing estradiol levels during stimulation (Fatum et al, 2013). Concurrently, a meta-analysis concluded that letrozole does not have a negative effect on the number of mature oocytes retrieved while suggesting a benefit of decreasing peak estradiol levels in patients and same stimulation length as hormone-sensitive cancers, signifying the safety of this protocol (Bonardi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lower estradiol level achieved by letrozole co-treatment may potentially confer lower risk to the patient; whether it translates to better prognosis of the patients' cancer disease would require further investigation. Current studies have echoed that letrozole is both safe in terms of obstetric outcomes and decreasing estradiol levels during stimulation (Fatum et al, 2013). Concurrently, a meta-analysis concluded that letrozole does not have a negative effect on the number of mature oocytes retrieved while suggesting a benefit of decreasing peak estradiol levels in patients and same stimulation length as hormone-sensitive cancers, signifying the safety of this protocol (Bonardi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A potential increase of the gonadotrophin effect due to the use of aromatase inhibitors cannot be ruled out [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is also not suitable in case of estrogen-sensitive cancers, such as breast and endometrial cancers as conventional ovarian stimulation may lead to high serum estrogen levels. For such cases, alternative ovarian stimulation protocols with either tamoxifen (selective estrogen receptor modulator) [51,52] or letrozole (aromatase inhibitor) [53][54][55][56][57][58] may be used. In addition, conventional ovarian stimulation may take up to several weeks and, in some cases, it may complicate into ovarian hyperstimulation syndrome making it not suitable for women with highly aggressive malignancies that require immediate anticancer treatment such as leukemia.…”
Section: Fertility Preservation and Restoration Options In Female Patmentioning
confidence: 99%